2021
DOI: 10.1155/2021/8896408
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Vibration System on Pain Reduction during Injection of Dental Anesthesia in Children: A Randomized Clinical Trial

Abstract: Background. The ‘‘gate control’’ theory suggests pain can be reduced by simultaneous activation of larger diameter nerve fibers using appropriate coldness, warmth, rubbing, pressure, or vibration. This study investigated the efficacy of a device combining cold and vibration, for needle-related procedural pain in children. Methodology. A total of 51 children aged 5–12 years participated in this randomized controlled clinical trial. Half of the children were in the control group and received maxillary buccal inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 31 publications
0
23
0
1
Order By: Relevance
“…The details of the excluded articles are listed in Table 1 . Seven studies were included in the final analysis [ 31 32 33 34 35 36 37 ]. The search results are presented as a flowchart in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The details of the excluded articles are listed in Table 1 . Seven studies were included in the final analysis [ 31 32 33 34 35 36 37 ]. The search results are presented as a flowchart in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of the included studies: All published studies from 2018-2021 are shown in Table 2 . Five of the seven studies followed a parallel-arm design [ 31 32 34 35 36 ], and two used the split-mouth design [ 33 37 ]. A total of 391 children, aged 4-12 years, received different dental injections, including infiltrations (both maxillary and mandibular) [ 34 36 ], maxillary infiltration alone [ 37 ], mandibular infiltration alone [ 32 ], infiltration and blocks [ 35 ], or inferior alveolar nerve block alone [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations